Chemical mutagenesis for improving potential of plants to remediate environments with heavy metal contaminants - Phang, Ing Chia; Taylor, H. Harry; Leong, David W. M. (Research Trends, 2012)
Toxic levels of heavy metals are increasingly posing threats to all organisms on earth. One possible remediation strategy involves the use of plants to remove toxic metals from contaminated soils. It is widely recognized that genetic improvement of plants with increased metal tolerance and uptake capacity would be required to enhance the practical prospect of this phytotechnology. In this paper, a summary of the studies using chemical mutagenesis as a breeding approach to obtain mutants with altered response to toxic metals is presented and discussed briefly. It is concluded that chemical mutagenesis probably deserves more attention as it is a valuable alternative to transgenic plant technology as far as generating plants with improved potential for phytoremediation of heavy metals in contaminated soils or for studying mechanisms of metal tolerance and uptake is concerned.